Improving MSME Accounting Financial Recording Skills Based on Android Applications - Ikhtiari, Kirana; Muslim, Muslim; Nurfadila, Nurfadila (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This community service project aimed to enhance the financial recording skills of Micro, Small, and Medium Enterprises (MSMEs) in Desa Kapita through hands-on training with Android-based accounting applications. Research Design and Methodology: The project employed a mixed-methods approach, including pre-and post-training evaluations via questionnaires, interviews, and practical exercises. Involving 25 SME owners in Desa Kapita, Kecamatan Bangkala, and Kabupaten Jeneponto, the training focused on the Wave application for transaction recording, expense management, and financial report generation. The program featured interactive workshops, simulated business scenarios, and follow-up mentoring. Findings and Discussion: Post-training evaluations revealed significant improvements in financial recording skills. 80% of participants developed a solid understanding of basic accounting concepts, and 85% effectively utilized the Wave application for managing finances. The training enhanced the accuracy and efficiency of transaction recording and financial report generation, leading to improved financial oversight and business decision-making. Implications: The findings indicate that targeted training can effectively close the digital literacy gap among SME owners, promoting the use of modern financial tools. Future efforts should incorporate regular mentoring and the creation of local support networks to maintain and broaden the benefits of digital financial management solutions for MSMEs.